Composite hydrogel for preventing and treating radiation-induced oral mucositis as well as preparation method and application of composite hydrogel

By using composite hydrogels prepared by PVA and lithium salts, the problem of difficulty in preventing and treating radioactive oral mucositis in the prior art is solved, especially in taste disorders, effective treatment effects are achieved, and good injectability is demonstrated and adhesion.

CN119405585APending Publication Date: 2025-02-11SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410611593.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-16
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent and treat radioactive oral mucositis, especially in light of the lack of effective methods for taste disorders caused by radiotherapy.

Method used

A composite hydrogel was prepared by using polyvinyl alcohol (PVA) as the main ingredient and combined with pharmaceutically acceptable lithium salts. The hydrogel forms a composite hydrogel with good drug carrier properties by mixing PVA with water and adding a lithium saline aqueous solution.

Benefits of technology

This composite hydrogel has good therapeutic effects in the treatment of radioactive oral mucositis, which can effectively relieve pain, reduce the severity of ulcers, and improve taste. Its injectability and adhesion also give it an advantage in clinical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405585A_ABST
    Figure CN119405585A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of medicines, and particularly relates to composite hydrogel for preventing and treating radiation-induced oral mucositis as well as a preparation method and application of the composite hydrogel. The hydrogel provided by the invention comprises the following components by concentration: 44 g / L-132g / L of polyvinyl alcohol; the concentration of the pharmaceutically acceptable lithium salt is 0.05 to 0.15 mmol / ml in terms of Li < + >. The composite hydrogel provided by the invention has a good treatment effect on radiation-induced oral mucositis, is convenient to smear, and can stay at an affected part for a long time. And meanwhile, the injection property is good. Therefore, the method has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medicine, and in particular relates to a composite hydrogel for preventing and treating radiation oral mucositis, and a preparation method and application thereof. Background Art

[0002] Radiation oral mucositis is a common complication of radiotherapy for patients with head and neck cancer, affecting more than 80% of patients. The symptoms such as pain, dry mouth, and loss of taste caused by radiation oral mucositis seriously impair the patient's quality of life and overall prognosis. However, there are currently few targeted treatments for radiation oral mucositis, and there is no method that is effective for taste disorders caused by radiation therapy.

[0003] Hydrogels constructed from polyvinyl alcohol (PVA) have been shown to have excellent physical and chemical properties. As a drug carrier, it has the effects of sustained and controlled release, good biocompatibility and stability; in addition, it has good adjustability, with a large number of -OH groups on the molecular chain, and a large number of weak non-covalent bonds such as hydrogen bonds and van der Waals forces inside the system. The porosity, elasticity and mechanical strength of PVA gel can be changed by adjusting the polymerization conditions, thereby affecting the release rate of drugs; good hydrophilicity, which is conducive to drug diffusion and release; high drug loading, the pore structure of PVA gel can accommodate a large amount of drugs, but the actual drug loading also depends on the interaction between PVA and specific drugs; high stability, PVA has a slow biodegradation rate; high modifiability, PVA has a simple chemical structure, the main chain is a carbon chain, the side chain is -OH, and it can be polymerized with a variety of polymers to form a double network or multi-level network structure; simple preparation and low cost.

[0004] Therefore, PVA hydrogel may have application potential in the repair of oral mucosal lesions. However, for the specific oral mucosal lesion of radiation oral mucositis, how to select active ingredients and construct PVA hydrogel with good therapeutic effect is still an urgent problem to be solved in this field. Summary of the invention

[0005] In view of the problems of the prior art, the present invention provides a composite hydrogel for preventing and treating radiation oral mucositis and its preparation method and use

[0006] A composite hydrogel for preventing and treating radiation oral mucositis, comprising components in the following concentrations:

[0007] Polyvinyl alcohol 44g / L-132g / L;

[0008] Pharmaceutically acceptable lithium salts, Li + The calculated concentration is 0.05-0.15mmol / ml.

[0009] Preferably, the following concentrations are included:

[0010] Polyvinyl alcohol 88g / L;

[0011] Pharmaceutically acceptable lithium salts, Li + The total concentration is 0.15mmol / ml.

[0012] Preferably, the molecular weight of the polyvinyl alcohol is 146000-186000 g / mol.

[0013] Preferably, the pharmaceutically acceptable lithium salt is selected from at least one of lithium carbonate, lithium bicarbonate or lithium citrate.

[0014] Preferably, the composite hydrogel is prepared by mixing polyvinyl alcohol with water, then adding a pharmaceutically acceptable lithium salt aqueous solution, dissolving, and heating to obtain the composite hydrogel.

[0015] Preferably, the heating temperature is 100-130° C.; and / or, stirring is performed simultaneously during the heating process.

[0016] The present invention also provides a method for preparing the composite hydrogel, comprising: mixing polyvinyl alcohol with water, then adding a pharmaceutically acceptable lithium salt, dissolving, and heating to obtain the composite hydrogel.

[0017] Preferably, the heating temperature is 100-130° C.; and / or, stirring is performed simultaneously during the heating process.

[0018] The present invention also provides use of the composite hydrogel in preparing a medicament for preventing and / or treating radiation oral mucositis.

[0019] The present invention also provides a medicine for preventing and / or treating radiation oral mucositis, which is prepared by using the composite hydrogel as an active ingredient and adding pharmaceutically acceptable auxiliary materials.

[0020] The present invention provides a composite hydrogel for radiation oral mucositis by screening the composite hydrogel components and the dosage thereof. The composite hydrogel of the present invention has good therapeutic effect, is easy to apply, and can stay on the affected area for a long time. At the same time, it also has good injectability. Therefore, the present invention has a good application prospect.

[0021] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0022] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The drug loading and application potential experimental results of PVA-Li hydrogel; (A) Frequency scan and viscosity curve of hydrogel (from left to right are the frequency scan and viscosity curve of composite hydrogel containing lithium carbonate and lithium citrate); (B) SEM image of hydrogel; (C) Maximum adhesion force of hydrogel; (D) Lithium ion sustained release curve of hydrogel.

[0024] Figure 2 The effect of PVA-Li hydrogel in the preventive treatment of radiation oral mucositis; (A) Schematic diagram of the preparation of the animal model of radiation oral mucositis; (B) Weight changes of animals in each group; (C) The severity of oral ulcers in animals in each group.

[0025] Figure 3 The effect of PVA-Li hydrogel in the preventive treatment of radiation-induced oral mucositis; (A) the taste changes of animals in each group; (B) the severity of oral ulcers in animals in each group treated with hydrogels of different lithium ion concentrations; (C) HE staining images of the dorsum and ventral tongue mucosa of animals in each group. DETAILED DESCRIPTION

[0026] In the following examples and experimental examples, reagents and raw materials not specifically described are all commercially available products.

[0027] Example 1 PVA composite hydrogel

[0028] The hydrogel of this embodiment includes the following components in concentrations:

[0029] Polyvinyl alcohol (PVA-1799, Mw 146000-186000 g / mol, Sigma-Aldrich) 88 g / L, lithium carbonate 0.05 mmol / ml.

[0030] The preparation method is as follows: PVA-1799 and double distilled water are weighed and mixed, lithium carbonate is added to the solution, ultrasonically dissolved for 5 minutes, heated to 130° C., and magnetically stirred for 1 hour until the PVA particles in the solution are completely dissolved.

[0031] Example 2 PVA composite hydrogel

[0032] The hydrogel of this embodiment includes the following components in concentrations:

[0033] Polyvinyl alcohol (PVA-1799, Mw 146000-186000 g / mol, Sigma-Aldrich, USA) 132 g / L,

[0034] Lithium citrate 0.05mmol / ml.

[0035] The preparation method is the same as that in Example 1.

[0036] Example 3 PVA composite hydrogel

[0037] The hydrogel of this embodiment includes the following components in concentrations:

[0038] Polyvinyl alcohol (PVA-1799, Mw 146000-186000 g / mol, Sigma-Aldrich, USA) 44 g / L,

[0039] Lithium citrate 0.15mmol / ml.

[0040] The preparation method is the same as that in Example 1.

[0041] The technical solution of the present invention is further illustrated by experiments below.

[0042] Experimental Example 1 PVA concentration optimization

[0043] 1. Experimental Methods

[0044] ① Injectability: According to the method of Example 1 above (or adjusting the amount of PVA, the amounts of other reagents and the preparation are the same as in Example 1), hydrogels with PVA concentrations of 44 g / L, 88 g / L, 132 g / L, and 176 g / L were prepared, respectively, and placed in a 1 ml injection needle to investigate the injectability of the hydrogel.

[0045] ②Viscosity test of hydrogel: The viscosity of PVA composite hydrogel was studied using Anton PaarPhysica MCR 302 rheometer (Austria). A flat plate with a diameter of 25 mm was selected as the oscillation mode. PVA composite hydrogel was prepared according to the above method. The gel was transferred to a flat plate (25°C), and the excess sample was scraped off and the viscosity test was performed at a shear rate of 0.1 to 100 s.

[0046] 2. Experimental Results

[0047] like Figure 1As shown in A, the injectability experiment shows that the PVA concentration is 44g / L, 88g / L, 132g / L, and 176g / L. The injectability is good when the concentration is 44g / L and 88g / L, the injectability is general when the concentration is 132g / L, and basically continuous injection can be achieved, and the injectability is poor when the concentration is 176g / L. However, the maximum adhesion of PVA is 0.7kPa and 5.3kPa when the concentration is 44g / L and 88g / L, respectively, while the maximum adhesion can reach 23.5kPa and 50.9kPa when the concentration is 132g / L and 176g / L. By screening the drug loading conditions of PVA concentrations of 44g / L, 88g / L, 132g / L and 176g / L, it was finally found that PVA with a concentration of 88g / L is more convenient to apply to the oral mucosa and can stay on the mouse tongue for a long time. At the same time, it also has good injectability. After drug loading, PVA hydrogel can form a relatively stable state with lithium ions.

[0048] Experimental Example 2 Drug loading and application potential of PVA composite hydrogel

[0049] 1. Experimental Methods

[0050] 1. Sample description

[0051] PVA-lithium carbonate (preparation method is the same as in Example 1): PVA concentration is 88 g / L, lithium carbonate concentration is 0.075 mmol / ml (Li + Concentration 0.15mmol / ml)

[0052] PVA-lithium citrate (preparation method is the same as in Example 1): PVA concentration is 88 g / L, lithium citrate concentration is 0.05 mmol / ml (Li + Concentration 0.15mmol / ml)

[0053] 2. Description of detection method:

[0054] ① Rheological testing of hydrogels: The rheological behavior of PVA composite hydrogels was studied using an Anton PaarPhysica MCR 302 rheometer (Austria). The storage modulus (G') and loss modulus (G") of the hydrogel were measured to determine its viscoelastic characteristics. A flat plate with a diameter of 25 mm was selected as the oscillation mode. The PVA composite hydrogel was prepared according to the above method. The gel was transferred to a flat plate (25°C), and the test was started after scraping off the excess sample. The maximum adhesion was carried out at room temperature (25°C), and the frequency sweep experiment was carried out at 0.1% strain in the frequency range of 0.1 to 100 Hz. Viscosity tests were performed at a shear rate of 0.1 to 100 s. All tests were performed at least three times.

[0055] ② Scanning electron microscopy (SEM): The morphology of the PVA composite hydrogel was observed using a high-resolution INSPECT F50 scanning electron microscope (SEM). The hydrogel was freeze-dried for 24 hours and attached to a silicon wafer. Then, the hydrogel was examined using a scanning electron microscope.

[0056] ③Sustained release: The sustained release characteristics of PVA composite hydrogel were tested using a contrAA 800 continuous light source atomic absorption spectrometer AAS (Jena, Germany). The hydrogel samples were pre-digested with high-grade pure nitric acid to remove the remaining metal ions in the samples, and the concentration of lithium ions in the hydrogel samples was measured at 670.8nm.

[0057] 2. Experimental Results

[0058] Through the performance verification of PVA composite hydrogel (PVA-Li) Figure 1 BE), found that:

[0059] ① Regardless of whether lithium carbonate or lithium citrate is used as the lithium ion donor, PVA-Li can form a stable hydrogel, and the hydrogel has a shear-thinning property, that is, as the shear rate increases, the viscosity of the hydrogel decreases, indicating that the hydrogel is injectable;

[0060] ② Scanning electron microscopy (SEM): PVA-Li hydrogel has a large number of microporous structures on its surface, which can accommodate more drug molecules and water molecules, thereby further increasing the drug loading capacity; in addition, the size, shape and other parameters of the microporous structure can be adjusted to meet different clinical needs;

[0061] ③ Maximum adhesion: Rheometer test shows that the maximum adhesion can reach 6-7kPa. During administration, the hydrogel can adhere firmly to the surface of the oral mucosa, increasing the administration time;

[0062] ④ Sustained release: Atomic absorption spectroscopy was used to measure the concentration of lithium ions released by PVA-Li hydrogel in the time periods of 0h, 6h, 12h, 24h and 48h. The experimental results showed that PVA, as a carrier, can achieve bimodal controlled release behavior, that is, a large amount of lithium ions are released in the first 12h, which quickly acts on the administration site, and after 12h, lithium ions are slowly released to achieve the effect of continuous administration. Although PVA-Li hydrogel shows different lithium ion release concentrations with lithium citrate and lithium carbonate as donors, the two hydrogels show similar release patterns, which also confirms that PVA has good application potential in drug delivery.

[0063] The above experimental results show that the PVA composite hydrogel provided by the present invention has good injectability, adhesion and drug loading capacity.

[0064] Experimental Example 3: Preventive treatment of radiation oral mucositis with PVA composite hydrogel

[0065] 1. Experimental Methods

[0066] Mice (Balb / c, male, 7-8 weeks old) were fixed and placed in an irradiator. The area below the neck was covered with a lead plate, leaving only the head exposed. Irradiation was performed at an X-ray dose of 3gy / d (160KV, 25mA). The modeling plan was irradiation for 5 days, rest for 2 days, and an additional irradiation of 12gy was performed on the first day of the third week. The mice were killed on the 21st day of modeling and samples were taken to test the effectiveness of the treatment of radiation oral mucositis.

[0067] The experimental groups are as follows:

[0068] Hydrogel group: 0.15mmol / ml Li was applied orally daily from 3 days before irradiation to the 11th day after irradiation. + and 88g / LPVA of PVA-lithium carbonate or PVA-lithium citrate hydrogel about 200ul (model Figure 2 A) Solution application group: 0.15mmol / ml Li solution was applied to the oral cavity daily from 3 days before irradiation to the 11th day after irradiation. + About 200ul of lithium carbonate or lithium citrate aqueous solution (mode Figure 2 A). Untreated group: Apply about 200ul of normal saline to the oral cavity every day from 3 days before irradiation to the 11th day after irradiation (mode Figure 2 A). Blank group: no treatment.

[0069] In addition, the concentrations of 0.05, 0.1, and 0.15 mmol / ml Li + The gradient exploration of the application of PVA-lithium citrate hydrogel, the hydrogel sample components used were 0.017mmol / ml lithium citrate + 88g / L PVA, 0.333mmol / ml lithium citrate + 88g / L PVA, 0.05mmol / ml lithium citrate + 88g / L PVA (the above samples were prepared according to the method of Example 1).

[0070] 2. Experimental Results

[0071] The results are as follows Figure 2 As shown, PVA-Li hydrogel alleviated the weight loss of radiotherapy mice ( Figure 2 B), significantly reduced the ulcer area and severity of radiation oral mucositis ( Figure 2 C) and effectively improved the taste of mice ( Figure 3 A), and hydrogel coating is better than solution coating, and lithium citrate is better than lithium carbonate. In addition, within a certain range, the higher the lithium ion concentration in the gel, the better the effect of preventing and treating radiation oral mucositis, which is dose-dependent ( Figure 3B). Observation under a microscope showed that PVA-Li hydrogel played a good protective role against the damage of reduced thickness and inflammatory infiltration of tongue mucosa in mice after irradiation ( Figure 3 C).

[0072] Through the above experiments, it can be seen that the PVA composite hydrogel provided by the present invention has a good therapeutic effect on radiation oral mucositis. In addition, lithium citrate is selected as the lithium salt, which has a better therapeutic effect.

[0073] It can be seen from the above embodiments and experimental examples that the present invention constructs a PVA hydrogel with good therapeutic effect for radiation oral mucositis and has a good application prospect.

Claims

1. A composite hydrogel for preventing and treating radiation oral mucositis, characterized in that: The following concentrations of components are included: Polyvinyl alcohol 44g / L-132g / L; Pharmaceutically acceptable lithium salts, Li + The calculated concentration is 0.05-0.15mmol / ml.

2. The composite hydrogel for preventing and treating radiation oral mucositis according to claim 1, characterized in that: The following concentrations of components are included: Polyvinyl alcohol 88g / L; Pharmaceutically acceptable lithium salts, Li + The total concentration is 0.15mmol / ml.

3. The composite hydrogel according to claim 1, characterized in that: The molecular weight of the polyvinyl alcohol is 146000-186000 g / mol.

4. The composite hydrogel according to claim 1, characterized in that: The pharmaceutically acceptable lithium salt is selected from at least one of lithium carbonate, lithium bicarbonate or lithium citrate.

5. The composite hydrogel according to claim 1, characterized in that: The preparation method of the composite hydrogel is as follows: polyvinyl alcohol is mixed with water, and then a pharmaceutically acceptable lithium salt aqueous solution is added, dissolved, and heated to obtain the composite hydrogel.

6. The composite hydrogel according to claim 5, characterized in that: The heating temperature is 100-130° C.; and / or, stirring is performed during the heating process.

7. The method for preparing the composite hydrogel according to any one of claims 1 to 6, characterized in that: include: The polyvinyl alcohol is mixed with water, and then a pharmaceutically acceptable lithium salt is added, dissolved, and heated to obtain the product.

8. The preparation method according to claim 7, characterized in that: The heating temperature is 100-130° C.; and / or, stirring is performed during the heating process.

9. Use of the composite hydrogel according to any one of claims 1 to 6 in the preparation of a medicament for preventing and / or treating radiation oral mucositis.

10. A drug for preventing and / or treating radiation oral mucositis, characterized in that: The composite hydrogel is prepared by taking the composite hydrogel described in any one of claims 1 to 6 as an active ingredient and adding pharmaceutically acceptable auxiliary materials.

Citation Information

Patent Citations

  • Preparation method of PVA-based 32P radioactive therapy hydrogel applicator

    CN116983464A

  • New dosage regimen for a composition comprising brimonidine for use thereof in the prevention and treatment of skin damage resulting from radiation

    WO2024013283A1